Diseño y construcción de una máquina semiautomática moldeadora de figuras en acero ASTM A36, para la empresa pro-acero ubicada en el cantón Latacunga, provincia de Cotopaxi. - Chicaiza Guagchinga, Edison Ramiro (2022)
The following technological proposal presents a response to the requirement of the Pro-Acero microenterprise, demanding the development of a semi-automatic machine for the elaboration of the volute-type figure made of steel. In order to provide a solution to this requirement, it was necessary to research bibliographic sources, videos and the application of the knowledge that has been acquired in the course of academic life and as future professionals, where it will be reflected from the preliminary design to the final finish of the machine. A semi-automatic figure molding machine was built in ASTM A36 steel, which does the work starting from the most internal point possible until finishing with the end of the desired figure, using square and round bars of 8 mm, 9 mm and 12 platens. and 19 mm with a thickness of 3, 4 and 6 mm, this being the matrix, coupled to the axis of the geared motor whose transmission of movement is made through sprockets of 21 teeth for the driving one and 21 teeth for the driven sprocket, whose movement It is transmitted by a 40 pitch chain, in order to obtain the desired product. For the design and construction of the machine, many aspects were taken into account such as machine dimensions, sprocket diameters, calculations to determine the effort suffered by the particular geared motor and therefore its sizing. The construction and assembly is based on the plans developed by the researchers during the course of this project. Once the machine was built, it proceeded to its first operational tests, and finally obtaining the desired results.